Valuing the Aspirations of the Community: The Origins of a Community-University Partnership - Jake D. Winfield; Sara Fiorot; Catherine Pressimone Beckowski; James Earl Davis (The University of Alabama, 2022)
Universities are increasingly prioritizing engagement and collaboration with their local communities. While such partnerships can be mutually beneficial, they can often perpetuate and exacerbate power differentials, particularly when the community partners belong to racially minoritized groups. This qualitative paper examines the founding of a community-university partnership between a Black, low-income community and a predominantly White university. Through the theoretical framework of aspirational capital, we find that valuing the experiences and aspirations of the community helped establish a more equitable partnership forged to support a community-led, culturally relevant after-school program. Centering the aspirations of Black community members and the epistemologies of the Black women on the program staff also served to acknowledge and address power imbalances at the founding stages of the partnership. Recognizing and valuing the aspirational capital of community members also positively impacted the university-based staff's ability to function as boundary spanners between the university and community who could adequately articulate the desires and needs of program staff. We argue that by recognizing and valuing the aspirational capital already present in low-income Black communities, universities can create more equitable partnerships for positive social change.